Analisis Persepsi Konsumen terhadap Produk Minyak Sawit Merah Sebagai Minyak Kesehatan (Studi Kasus: Perumahan Ciomas Permai, Bogor) - Muhammad Alif Bardhani; Fransiska Rungkat Zakaria; Nurheni Sri Palupi (Institut Pertanian Bogor, 2009)
Product of red palm oil is a new product which is still not marketed yet insufficient quantity so that it is not recognized by many people. Because of that, it needs promotion about the benefit and quality for the consumer. The approach in this research is market or selling the product of red palm oil to the respondent through direct marketing (door to door), and at the same time do the analysis of consumer’s perception to the product of red palm oil. In general the aim of this research is to know consumer’s perception in getting decision of buying and strategy alternative which can be done in marketing of red palm oil in Perumahan Ciomas Permai, Bogor. Location of this research is in Perumahan Ciomas Permai, Blok B Desa Ciapus Kecamatan Ciomas Kabupaten Bogor.The method of this research is case study with descriptive and quantitative analysis with multiple regression. The processing and data analysis were done with application of Microsoft Excel, which is shown in the form of tabulation and correlation matrix and analysis multiple regression linear with counting use computer program SPSS. The number of respondent were 35 people who represent middle household. Based on the research, through direct marketing and consumer’s analysis, it was found that there were four factors which influence the process of buying decision red palm oil namely price, color, content of nutrient and the packaging. The strategy of marketing which can be done for the product of red palm oil is maintain and improve the quality of red palm oil (the hygienic control, quality, purity, color and nutrient content), giving a discount in a certain sales, promotion by distributing brochure and leaflet, service of delivery and guarantee the continuity of red palm oil availability.